SAS and Elite Forces guide prisoner of war escape & evasion : how to survive behind enemy lines, from the world's elite military units - McNab, Chris 1970- (Lyons Press, 2012)
With more than 120 black- & -white drawings and with easy-to-follow text, The POW How To Escape Handbook is for anyone who wants to know how to survive in the most stressful of circumstances and emerge a winner. Presented in a handy, pocketsize format, this is a book you could take with you into the field. And it could save your life.